Bacterial Contamination that Causes Food Poisoning in Fruit Salads in Banjarbaru Indonesia - Nurmalasari Nurmalasari; Ekrima Dayanti; Ahmad Muhlisin; Ratih Dewi Dwiyanti; Erfan Roebiakto (Tropical Health and Medical Research, 2021)
Fruit salad is one food combination that often causes food poisoning because it contains cheese and milk. This study aims to analyze the bacterial contamination that causes food poisoning in fruit salads sold in Banjarbaru, Indonesia, and the factors that play a role in such pollution. Food poisoning from fruit salad can be anticipated by knowing bacterial contamination and the factors that play a role in it. This study uses an observational method with a cross-sectional design. The sample in this study was fruit salads from 18 different producers sold in Banjarbaru, Indonesia. Fruit salad with criteria containing fruit, cheese, and mayonnaise. The bacteria that caused food poisoning to find in the fruit salad, namely Staphylococcus aureus, and Bacillus cereus. In conclusion, his research found the contamination of bacteria that cause food poisoning in Fruit Salad in Banjarbaru City with a percentage of 22 percent. The types of bacteria are Staphylococcus aureus (11 percent) and Bacillus cereus (11 percent). It recommends that salad sellers wash their hands before processing, use running water to wash fruit, and use secure salad packaging.